Atitudes e práticas relacionadas à prevenção da aids em jovens de escolas públicas da cidade de Curitiba-Pr - Alencar, Cristian Guilherme Valeski de (2013)
The present study aimed to describe attitudes and practices related to AIDS prevention among high-school students from state schools in Curitiba, Parana State/Brazil, and analyze related factors to the use of condoms in vaginal intercourses with regular and occasional partners. Four hundred (400) young students from the last year of high school participated in this research. A cluster sampling was carried out with the participation of a school from each region of the city. Data were gathered by means of a questionnaire on: demographic data, risk perception, capacity of communication about sex/AIDS with friends, social support for the use of condoms, beliefs on the use of condoms, sexual behavior, reasons for not using condoms, capacity to communicate about sex/AIDS with a partner, capacity to negotiate the use of condoms. For data analysis of the first article, descriptive statistics was used, and in the second article, Pearson’s Chi-Square test (p<0.05) was used. Results evidenced that 39% of students made use of condoms during vaginal intercourses with regular partners, and 61% with casual partners. Knowing your partner (89%) was the main mentioned reason for not using condoms. As for condoms, 59% believe they reduce pleasure, and 45% believe they hinder the intercourse. Talking to friends, 32% reported discussing the use of condoms, and talking to partners, the use of 9 condoms was discussed by 52% of the students, although 30% stated that they would have sex with the partner even if he/she did not want to use a condom. As for the risk perception, 65% stated that people with the same sexual practices as they may get infected by AIDS. Results evidenced that subjects who made higher use of condoms during their vaginal intercourses with regular and occasional partners, were the ones who also made higher use of condoms in other sexual practices, the ones who talked more to friends and partners about the use of condoms, the ones who present a greater risk perception of getting infected by HIV and have more positive opinions about condoms. Data showed the need for implementing projects which aim at reducing individual and social vulnerability to HIV of students from state schools in Curitiba, and enabled to conclude that there is a positive correlation between the use of condoms in vaginal intercourses to other sexual practices.